PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA SMA TENTANG ALAT-ALAT OPTIK MELALUI MODEL PEMBELAJARAN ASSURE - Sumalinda, Nining Juandini; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted with the intention of helping the teacher in creating a learning material on optical devices based on learning technology centered on students through the ASSURE model. The ASSURE model has an extension Analyze lerner characteristics, State performance objectives, Select Methods, media, and materials,Â  Utilize materials, Requere learner participation, Evaluate and revise. To determine the development process of learning tools based on ASSURE models on the optical tools material to achieve learning objectives and determine the level of feasibility based on the questionnaire to the teachers. In its development using the development based on the development theory of Borg and Gall which is limited as follow 7 initial stages, namely; 1) potential problems; 2) information gathering; 3) product design; 4) design validation; 5) design revision; 6) manufacturing of products; and 7) limited trial. Based on the data analysis, the result showed that RPP developed was declared feasible with the format and arrangement of RPP (92%), RPP content (87%), and RPP reflecting ASSURE learning steps (96%) with very high validation criteria 81% - 100%. In the future, it is expected that the development of learning tools using the ASSURE model in other materials.Â Keywords: Development, ASSURE Model, Telescope, Learning Devices